HUBUNGAN PERAN GURU DENGAN PERILAKU DISIPLIN ANAK DI TK SE-KECAMATAN PONTIANAK UTARA - Sinta, Yuliana; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to determine and describe the relationship of teacher roles with discipline behavior of children in North Pontianak Sub-district. The method used is descriptive method with quantitative approach and the form of research is interrelationship studies. Data sources are 50 teachers and 50 children aged 5-6 years. The result of data analysis showed a strong correlation between teacher role and the behavior of 5-6 year old child in North Pontianak Kindergarten of 0.909 with very high category, r_xy> r_tabel (0,909> 0,284) so that the correlation result is convincing or significant . Keywords: Teacher Role, Early Childhood Discipline